Transformasi Teknologi Digital dan Ramah Lingkungan untuk Transportasi Masa Depan pada Industri Maritim - Haris Padilah; Tini Utami; Devy Kusumaningrum (Politeknik Bumi Akpelni, 2025)
The maritime world is entering a new era that demands a balance between digitalization and environmental sustainability. This sector is not only challenged by technological advancements, but also by ensuring that innovations remain environmentally friendly. This study aims to examine the transformation of digital and environmentally friendly technologies in the maritime transportation sector. This study uses a literature review method. It shows that organizational, technological, and environmental factors influence organizational digitalization in the maritime transportation sector. Digitalization encompasses collaboration between organizations and new partners to develop new digital solutions (including through participation in projects related to digitalization and/or digital transformation) and digitize internal and external business processes. Supported by the development of environmental technologies, it is crucial for a more sustainable approach. One such technology is the hybrid propeller system, which helps reduce greenhouse gas emissions from the ocean. Furthermore, energy storage systems, solar panels, and wind turbines are innovative ways to improve energy efficiency. However, these technologies also require significant infrastructure investment and high-quality power generation, and the greatest challenge in using alternative fuels is the limited infrastructure in ports worldwide.